PRINSIP SYARI’AH DALAM STRATEGI PEMASARAN PRODUK PEMBIAYAAN MURABAHAH LEMBAGA KEUANGAN SYARIAH BAITUL MAL WAT TAMWIL(BMT) - Siswadi Siswadi; Rohman (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2019)
Baitul Mal Wattamwil (BMT) build and develops an economic structure and a structure of civil society that is justly prosperous, progressing, and prosperous with justice based on Sharia and the blessing of Allah SWT. Murabahah product is a contract of purchase and purchase financing where the principal price and profit margin are known and agreed upon by both parties, at which time the transaction is handed over, the goods are traded while the payment can be paid in installments The pillars of murabahah financing products that must be fulfilled in transactions include; (1) the contractor, namely bai ’(seller) in this case is BMT and Musytari (buyer), in this case, is the customer who needs and needs goods. (2) The object of the contract is mabi '(merchandise), tsaman (price), (3) Shigah, ijab and qabul. Sharia marketing has four characters namely Rabaniyah, Akhlaqiyah, Al-Waqiiyah and Insyaniyah. These characters will get a marketing that is in accordance with the principles of shari'ah and distinguishes it from other marketing (non-shari'ah). The character of Rabaniyah must be possessed by an Islamic marketer who is convinced that Allah SWT is always close to him and watches over him when he does all kinds of business.